CULTIVATING RESILIENCE: A MULTI-LEVEL ANALYSIS OF ORGANIZATIONAL CULTURE AND BUREAUCRATIC AGILITY IN THE FACE OF SYSTEMIC CRISES - Mulyaningsih Mulyaningsih (Scientechno: Journal of Science and Technology, 2026)
Organizational resilience has become an essential factor for navigating systemic crises, yet the interplay between organizational culture and bureaucratic agility remains underexplored. This study investigates how these two elements collectively contribute to an organization’s ability to respond to and recover from crises. The main objective of the research is to examine the relationship between organizational culture, bureaucratic agility, and resilience, particularly during systemic crises. A multi-level analysis is conducted through a comparative study across public, private, and non-profit sectors, utilizing both qualitative (interviews and focus groups) and quantitative (surveys) methods. The results show that organizations with a strong, adaptable culture and flexible bureaucratic systems exhibit higher levels of resilience, enabling quicker adaptation and more effective crisis management. The private sector, with its emphasis on innovation and agility, demonstrated superior resilience compared to the more rigid structures found in the public and non-profit sectors. This study concludes that both organizational culture and bureaucratic agility are crucial in cultivating resilience, with their combined influence offering a more effective approach to crisis preparedness and response. The findings underscore the need for organizations to integrate cultural and structural flexibility to enhance resilience in the face of uncertainty.